A NEW TECTONIC SCENARIO FOR THE SANANDAJ-SIRJAN ZONE (IRAN) - Ghasemi A.; Talbot C.J. (My University, 2006)
Recent geochemical studies of volcanic rocks forming part of the ophiolites within the Zagros and Naien-Baft orogen indicate that most of them were developed as supra-subduction ophiolites in intra-oceanic island arc environments. Intra-oceanic island arcs and ophiolites now forming the Naien-Baft zone were emplaced southwestward onto the northeastern margin of the South Sanandaj-Sirjan Zone, while those now in the High Zagros were emplaced southwestward onto the northern margin of Arabia. Thereafter, subduction continued on opposite sides of the remnant oceans. The floor of Neo-Tethys Ocean was subducted at a low angle beneath the entire Sanandaj-Sirjan Zone, and the floor of the Naien-Baft Ocean was subducted beneath the Central Iranian Micro-continent. The Naien-Baft Ocean extended into North-West Iran only temporarily. This failed ocean arm (between the Urumieh-Dokhtar Magmatic Assemblage and the main Zagros Thrust) was filled by thick Upper Triassic-Upper Jurassic sediments. The Naien-Baft Ocean finally closed in the Paleocene and Neo-Tethys closed in the Early to Middle Eocene. After Arabia was sutured to Iran, the Urumieh-Dokhtar Magmatic Assemblage recorded slab break-off in the Middle Eocene. © 2005 Elsevier Ltd. All rights reserved.
Keywords: NEO-TETHYAN OCEAN; SLAB BREAK-OFF; SUPRA-SUBDUCTION OPHIOLITE; ZAGROS OROGENIC BELT; Jurassic; Triassic; Eocene; Paleocene; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Triassic; Мезозой::Триасовая; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Кайнозой::Палеоген::Палеоцен